Unveiling a symptomatic disease in custard apples: effective management strategies against fruit degradation - Akila, R; ChelviRamessh; Balasubramanian, P; Kumar, C S (Plant Science Today, 2025)
Annona squamosa is a tropical fruit susceptible to various diseases that significantly impact its yield and quality of the fruits. Colletotrichum spp. rank among the top ten most destructive fungal pathogens globally, occupying the 8th position due to their significant impact on agriculture. These fungi are hemibiotrophic in nature, with over 1,000 known species, and most crops are susceptible to at least one of these. They cause various diseases, including leaf spots, blights, and fruit rots. Symptoms manifest on horticultural crops' leaves, flowers, fruits, and branches, often resulting in substantial yield losses. Colletotrichum species exhibit a latency mechanism that can exacerbate damage during post-harvest storage, leading to up to 80 % production losses in some instances. Experiments were carried out in Randomized Block Design with seven treatments and three replications at the C1 block of Regional Research Station, TNAU, Aruppukottai, Virudhunagar District, Tamil Nadu, to identify and manage the pathogens causing leaf spot and fruit rot in custard apples. Pathogens isolated from the rotten fruit rind and mesocarp were identified as Colletotrichum siamense (Acc No: OM736073) and Colletotrichum gloeosporioides (Acc No: OM736066), respectively, through morphological and molecular analyses. The isolated DNA of the respective pathogens were amplified using PCR with ITS 1 & 4 primers. Then, the amplified product (550bp) was sequenced and submitted to the NCBI website. Pathogenicity tests confirmed these isolates as the causative agents for the leaf spot and fruit rot symptoms. Field experiments were conducted for two consecutive years to evaluate the efficacy of various treatments in managing leaf spot and fruit rot diseases. Before spraying, the leaf spot and fruit rot incidence are 77 and 27, respectively, in the control plot. The combined fungicide formulation, Tebuconazole 25 % + Trifloxystrobin 50 % WG (0.1 %), showed the highest disease reduction (60.44 %) and yield enhancement (15.50 kg/tree). The spraying of neem seed kernel extract (5 %) and Bacillus subtilis (0.5 %) also resulted in significant disease reduction and yield improvement. The study highlights the importance of combining chemical and biocontrol agents with integrated disease management strategies to manage custard apple diseases effectively. Neem products are always safe for the environment, Humans and animals and when they are used in correct concentration they won't leave any residues. Likewise, biocontrol agents are target-specific and never harm the beneficial microbes in soil and the plant system.